18F-FDG PET/CT imaging of vulva cancer recurrence: A comparison of PET-derived metabolic parameters between women with and without HIV infection - Mokoala, Kgomotso M.G.; Lawal, Ismaheel O.; Lengana, Thabo; Popoola, Gbenga O.; Boshomane, Tebatso M.G.; Mokgoro, Neo P.; Vorster, Mariza; Sathekge, Mike M. (Nuklearmedizin - NuclearMedicine, 2020)
Objective To assess the patterns of recurrence of vulva cancer on 18F-FDG PET/CT and to compare the 18F-FDG PET metabolic metrics in patients with and without Human Immunodeficiency Virus (HIV).Methods Maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), metabolic tumour volume (MTV and total lesion glycolysis (TLG) were obtained on Flourine-18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT) images of women referred with suspected or confirmed vulva cancer recurrence. We compared HIV-infected and HIV-uninfected patients regarding pattern disease recurrence, age at diagnosis, and the PET-derived metabolic indices.Results We analyzed 33 patients with a mean age 50.76 ± 15.78 including 21 HIV-infected women. The majority of patients (94 %) had squamous cell carcinoma and 84.85 % were Blacks. Of the HIV-infected individuals, the median CD4 count was 526.0 cells/mm3 (IQR: 379.0–729.0). HIV infected patients were younger than the HIV uninfected at the time of diagnosis: 40.50 ± 8.87 vs 66.54 ± 9.71 respectively, p < 0.001. We found a local (vulvar) recurrence rate of 75.8 %. Nodal pelvic recurrences were higher in the HIV-infected patients than in the HIV uninfected patients (70 % vs 30 %, p = 0.027). Three patients had distant metastasis and all three were HIV-infected. There was a higher whole-body MTV and TLG among HIV-infected women compared with HIV-uninfected women, 103.39 vs 17.58 and 852.64 vs 101.79, respectively (p < 0.05 for both).Conclusion HIV-infected women are diagnosed with vulva cancer at a younger age. HIV-infected patients had a higher rate of pelvic lymph node recurrence. There is a higher tumor burden at vulva cancer recurrence among women with HIV infection.
Keywords: vulva cancer; HIV; 18F-FDG PET/CT; SUVmax; MTV